1999
DOI: 10.1002/(sici)1521-3773(19990503)38:9<1255::aid-anie1255>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A New CoII Complex as a Bulge-Specific Probe for DNA

Abstract: Bulge cleavage of two or three bases occurs when a DNA substrate is specifically cleaved oxidatively by [Co (tfa) (happ)] (see picture). Hydrogen peroxide is necessary for the activation of this octahedral complex, which suggests that hydroxyl radicals are the reactive species. The complex has no significant reactivity towards the corresponding sequence in a single-stranded DNA region, and it exhibits only a low affinity towards double-stranded DNA. happ=macrocyclic ligand based on 1,10-phenanthroline, tfa=tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 12 publications
(17 reference statements)
2
33
0
Order By: Relevance
“…Some of the previous reports show that hexamine cobalt complexes induce DNA condensation [23,24] and can be used to probe RNA hairpins [25]. Some of the cobalt(II) complexes, such as [Co(tfa)(happ)], are known to function as specific probe for DNA bulges due its ability to cleave DNA specifically [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the previous reports show that hexamine cobalt complexes induce DNA condensation [23,24] and can be used to probe RNA hairpins [25]. Some of the cobalt(II) complexes, such as [Co(tfa)(happ)], are known to function as specific probe for DNA bulges due its ability to cleave DNA specifically [26].…”
Section: Introductionmentioning
confidence: 99%
“…Vaidyanathan and Nair [15] have reported that cis-[Cr(dppz) 2 Cl 2 ] + complex binds to DNA by intercalation with a binding constant of 10 7 M À1 . Co (III) Xaa-Xaa-His-metallopeptides induce DNA strand scission upon photoirradiation [16] while oxygen/H 2 O 2 activated Co(II) complex of a macrocyclic ligand based on 1,10-phenanthroline acts as a bulge-specific probe for DNA [17] and vanadyl(IV) complexes derived from Nsalicylidene a-amino acids serve as efficient DNA photocleavage agents [18].…”
Section: Introductionmentioning
confidence: 99%
“…Varying the substitutive group or substituent position in the intercalative ligand can create some interesting differences in the space configuration and the electron density distribution of transition metal complexes, which will result in some differences in spectral properties and the DNA-binding behaviors of the complexes and will be helpful to more clearly understand the binding mechanism of transition metal complexes to DNA [6][7][8]. However, such studies mainly focus on the interaction of Ru(II) complexes with DNA, and the reports on the other metal complexes are relatively limited [9][10][11][12][13][14][15][16][17]. Our group has been synthesized some cobalt(III) mixedpolypyridyl complexes, which bind to DNA through an intercalative mode and promote photocleavage of plasmid pBR 322 DNA [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%